Studi Pengaruh Ukuran Pebble bed Terhadap Termal Hidrolik Pada Thorium Molten Salt Reactor Solid Fuel (TMSR-SF) Menggunakan COMSOL Multiphysics - I Gusti Ayu Putu Dwi Ekasari; Yanti Yulianti; Duwi Hariyanto; Gurum Ahmad Pauzi (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2026)
Abstract. The development of nuclear energy, particularly in the Thorium Molten Salt Reactor Solid Fuel (TMSR-SF) requires a deep understanding of thermal-hydraulic characteristics, including temperature, flow velocity, and pressure within the reactor core. This research aims to analyze the influence of pebble bed diameter on temperature and pressure, as well as to examine the impact of initial fluid flow conditions on fluid velocity within the TMSR-SF reactor core. Simulations were conducted by the Heat Transfer in Fluids and Laminar Flow modules in the COMSOL Multiphysics application. The simulation results show that the highest temperature difference percentage between the 6 cm and 9 cm pebble beds is 0.7%, while between the 6 cm and 12 cm pebble beds, it is 1.7%. Percentage the highest pressure drop over time was observed in the 6 cm pebble bed at 1.6%, followed by the 9 cm pebble bed at 1.4%, and the 12 cm pebble bed at 1.5%. Additionally, the percentage difference off the initial fluid flow rate decreasing was recorded at 0.09% between the 6 cm and 9 cm pebble beds and 0.26% between the 9 cm and 12 cm pebble beds. The 6 cm pebble bed diameter provides more optimal thermal-hydraulic performance, particularly in terms of temperature stability and fluid flow consistency, which are crucial for the efficiency and safety of TMSR-SF reactor operation Keywords: COMSOL Multiphysics, TMSR-SF, thermal hydraulics, pebble bed, diameter variations